Enantiospecific synthesis and filed evaluation of four stereoisomers of 10, 14-dimethyloctadec-1-ene, a sex pheromone component secreted by female moths of the apple leafminer. Issue 5 (4th May 2014) - Taguri, Tomonori; Yaginuma, Katuhiko; Yamamoto, Masanobu; Fujii, Toru; Ando, Tetsu
Abstract: All four stereoisomers of 10, 14-dimethyloctadec-1-ene, a sex pheromone component of the apple leafminer ( Lyonetia prunifoliella : Lepidoptera), were synthesized starting from ( R )- and ( S )-propylene oxide by applying stereospecific inversion of chiral secondary tosylates as a key step. Field evaluation showed that male moths of the Japanese population were selectively attracted by the (10 S, 14 S )-isomer and that the activity was not inhibited by the enantiomer.